A Case of Torsion in an Otherwise-Normal Ovary with a Giant Hematosalpinx Larger than Enlarged Ovary: Utilization of Diagnostic Laparoscopy for the Accurate Diagnosis - Sae Yu; Koji Yamanoi; Masumi Sunada; Sachiko Kitamura; Naoki Horikawa; Yoshitsugu Chigusa; Ken Yamaguchi; Akihito Horie; Junzo Hamanishi; Eiji Kondoh; Masaki Mandai (Case Reports in Obstetrics and Gynecology)
We report a case of torsion in an otherwise-normal ovary with a giant hematosalpinx. A 23-year-old woman presented with complaints of abdominal pain and nausea. At initial visit, there was few abnormal findings of imaging tests, and we made a diagnosis of ovarian hemorrhage. Three days later, she came back with increased symptoms, and we detected the mass of a complex solid cystic structure with a unilocular cyst much larger than solid component. A diagnostic laparoscopy was performed immediately, and we could make a diagnosis of torsion in an otherwise-normal ovary with a giant hematosalpinx. We performed a salpingectomy and could preserve her ovary. This is the first case of torsion in an otherwise-normal ovary with a giant hematosalpinx which enlarged to a greater extent than the ovary.